2006
DOI: 10.1007/0-387-26283-0_5
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Immune Cells in the Tumor Microenvironment

Abstract: Abstract:Keywords:Interactions between tumor infiltrating leukocytes and tumor cells have been of great interest because of the possibility that immune cells either interfere with tumor progression or actively promote tumor growth. The tumor microenvironment is shaped by cells entering it, and their functions reflect the local conditions. Successive changes occurring at the tumor site during tumor progression resemble chronic inflammation. This chronic inflammatory reaction seems to be largely orchestrated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
66
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(67 citation statements)
references
References 81 publications
1
66
0
Order By: Relevance
“…20 Several studies have described the diversity of tumor escape strategies and notably, alterations in T-cell receptor signaling, suppression of T-cell responses by T regulators, suppression of natural killer activity, and decreased expression of costimulatory molecules. 21 Furthermore, some studies have shown that immune cells can also contribute to promote tumor growth. Indeed, it has been described that tumorassociated macrophages stimulate tumor angiogenesis through VEGF secretion.…”
Section: Discussionmentioning
confidence: 99%
“…20 Several studies have described the diversity of tumor escape strategies and notably, alterations in T-cell receptor signaling, suppression of T-cell responses by T regulators, suppression of natural killer activity, and decreased expression of costimulatory molecules. 21 Furthermore, some studies have shown that immune cells can also contribute to promote tumor growth. Indeed, it has been described that tumorassociated macrophages stimulate tumor angiogenesis through VEGF secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Although being detrimental to tumour cells, the EBV-DNA load in hepatocellular carcinoma was found to be 1000-fold higher than in peripheral blood mononuclear cells (Sugawara et al, 2000;Tamada and Chen, 2006). It appears possible that the tumour controls and inactivates these cells, as described for other infiltrating leukocytes (De Visser et al, 2006;Whiteside, 2006).…”
Section: Discussionmentioning
confidence: 95%
“…They are, therefore, capable of remodelling connective tissue, stimulate invasion, migration, and growth of tumour cells, and induce neoangiogenesis (Dubuisson et al, 2000;Monvoisin et al, 2002). Furthermore, important cellular components of the tumour microenvironment are various types of leukocytes, including dendritic cells, natural killer cells, and tumour-associated macrophages (Robinson and Coussens, 2005;De Visser et al, 2006;Whiteside, 2006). Their interaction with tumour cells often results in immunotolerance through reduced immunogenicitiy of the tumour and incapacitation of immune cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, solid tumors are mostly recognized as "self" and they do not evoke efficient immune responses capable of eradicating tumors [148,149]. In contrast, it was found that these cells are actively recruited to neoplastic tissues by tumor cells and that high numbers of several types of leukocytes are associated with tumor progression [38,[150][151][152]. Nevertheless in some cancers, the presence of leukocytes is associated with a favorable prognosis [153].…”
Section: Leukocytesmentioning
confidence: 99%